Decentralization of industrial policy as strategic delegation - Karl Morasch (Universität Augsburg, Institut für Volkswirtschaftslehre, 2000)
What is the appropriate degree of centralization in the context of industrial policy? The basic advantage of centralization results from internalization of external effects. While most of the literature stresses the superior information of regional authorities as a countervailing force, the present paper discusses another argument in favor of decentralization: Delegation of authority to regional governments will improve the position of the home country in the policy game with a foreign government. In a linear Cournot oligopoly with two domestic regions delegation is shown to be profitable if the domestic industry comprises at least twice as many firms as the foreign industry.
urn:nbn:de:bvb:384-opus4-276792
Keywords: D43; F13; L13; L52; 330; Decentralization; Strategic delegation; Industrial policy; Oligopoly